DETERMINANTS OF ORIGINAL LOCAL GOVERNMENT REVENUE OF REGENCY/CITIES AT WEST SUMATRA PROVINCE IN 2020-2021 - Mulya Liza; Lili Wahyuni; Rita Dwi Putri (Jurnal Ekonomi, 2023)
Regions that are considered advanced are regions that have high Original Local Government Revenue (PAD). The high PAD received by a region is an assessment of the level of regional government dependence on the central government in terms of APBD funding. Regional Original Income consists of several revenues including Rural and Urban Land and Building Tax (PBB-P2) and Acquisition Duty of Right on Land and Building (BPHTB). This research aims to determine the effect of Rural and Urban Land and Building Tax (PBB-P2) and Acquisition Duty of Right on Land and Building (BPHTB) on Original Local Government Revenue (PAD). This type of research is quantitative research. The population of this research is all regencies/cities in West Sumatra. The sampling technique used was total sampling. The data used is the 2020-2021 West Sumatra Province Regency/City Regional Revenue and Expenditure Budget Realization Report. The research results show that Rural and Urban Land and Building Tax (PBB-P2) affects Original Local Government Revenue (PAD). Meanwhile, receipt of fees for the Acquisition Duty of Right on Land and Building (BPHTB) does not affect Original Local Government Revenue (PAD). Simultaneously, Rural and Urban Land and Building Tax (PBB-P2) and Acquisition Duty of Right on Land and Building (BPHTB) influence Original Local Government Revenue (PAD).